Comparison of psychological capital, self-compassion, and mental health between with overseas Chinese students and Taiwanese students in the Taiwan. (December 2021) - Chen, Po-Lin
Abstract: This research investigates the psychological capital (PsyCap), subjective well-being (SWB), and self-compassion (SC) components of mental health in a comparative study of overseas Chinese students (OCS) and Taiwanese students in a multicultural context. The participants in the study, which focuses broadly on the recent direction in psychology of positive psychology, were 1347 students from universities and colleges in Taiwan, including 362 Malaysian OCS, 213 Hong Kongese and Macanese OCS, and 772 Taiwanese students. A questionnaire using items from PsyCap, SC, and SWB was administered to the participants. The results of hierarchical regression analysis showed that the level of SC is more relevant for the influence of PsyCap on SWB in the range of PsyCap high scores than it is in the range of PsyCap scores at the low end, and SC is less relevant for the influence of PsyCap on depression at the high end of the PsyCap scale. The findings of the study offer useful insights and implications for researchers and practitioners who investigate well-being and the prevention and alleviation of depression and the specific relationships between PsyCap, SWB, and SC.